Immunogenicity of PE18, PE31, and PPE26 proteins from Mycobacterium tuberculosis in humans and mice - García-Bengoa, María; Vergara, Emil Joseph; Tran, Andy C.; Bossi, Lorenzo; Cooper, Andrea M.; Pearl, John E.; Mussá, Tufária; von Köckritz-Blickwede, Maren; Singh, Mahavir; Reljic, Rajko (Frontiers in Immunology, 2023)
Introduction The large family of PE and PPE proteins accounts for as much as 10% of the genome of Mycobacterium tuberculosis. In this study, we explored the immunogenicity of three proteins from this family, PE18, PE31, and PPE26, in humans and mice. Methods The investigation involved analyzing the immunoreactivity of the selected proteins using sera from TB patients, IGRA-positive household contacts, and IGRA-negative BCG vaccinated healthy donors from the TB endemic country Mozambique. Antigen-recall responses were examined in PBMC from these groups, including the evaluation of cellular responses in healthy unexposed individuals. Moreover, systemic priming and intranasal boosting with each protein, combined with the Quil-A adjuvant, were conducted in mice. Results We found that all three proteins are immunoreactive with sera from TB patients, IGRA-positive household contacts, and IGRA-negative BCG vaccinated healthy controls. Likewise, antigen-recall responses were induced in PBMC from all groups, and the proteins stimulated proliferation of peripheral blood mononuclear cells from healthy unexposed individuals. In mice, all three antigens induced IgG antibody responses in sera and predominantly IgG, rather than IgA, responses in bronchoalveolar lavage. Additionally, CD4+ and CD8+ effector memory T cell responses were observed in the spleen, with PE18 demonstrating the ability to induce tissue-resident memory T cells in the lungs. Discussion Having demonstrated immunogenicity in both humans and mice, the protective capacity of these antigens was evaluated by challenging immunized mice with low-dose aerosol of Mycobacterium tuberculosis H37Rv. The in vitro Mycobacterial Growth Inhibition Assay (MGIA) and assessment of viable bacteria in the lung did not demonstrate any ability of the vaccination protocol to reduce bacterial growth. We therefore concluded that these three specific PE/PPE proteins, while immunogenic in both humans and mice, were unable to confer protective immunity under these conditions.